Local Research Catalyzes National Surgical Planning; Comment on "Global Surgery - Informing National Strategies for Scaling Up Surgery in Sub-Saharan Africa" - Micah G. Katz; Raymond R. Price; Jade M. Nunez (Kerman University of Medical Sciences, 2018)
In 2015 the Lancet Commission on Global Surgery (LCoGS) argued that surgical care is important to national health systems along with the economic viability of countries. Gajewski and colleagues outlined how the Commission's blueprint has been implemented in sub-Saharan Africa, including two funded research projects that were integrated into national surgical plans. Here, we outline how the five processes proposed by Gajewski and colleagues are critical to integrate research, policy, and on-the-ground implementation. We also propose that, moving forward, the most pressing adjunct in many low- and middle-income countries (LMICs) may be a better characterization of rural surgical practices through rigorous research along with models that enable lessons to inform national policy.